Presuppositions in The Headline Structures of Skin1004 Selected Products - Luh Gede Dwiana Antika Premaputri; Galuh Febri Putra; Ni Ketut Widhiarcani Matradewi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The analysis discussed about the presupposition in the headline structures of Skin1004 selected products. The aims of the analysis were to describe the categories of presupposition, and to investigate the functions of presupposition. The source of the data was found in the headline structures of Skin1004 selected products, which collected from Skin1004 Official Shop e-commerce. The analysis research method was applying descriptive qualitative method. The theories of analysis were applying Yule (1996) categories of presupposition theory and Ge (2011) functions of presupposition theory. The results of the discussion were found four categories of presupposition, which consisted with total thirty-five data sources, namely, existential presuppositions, factive presuppositions, lexical presuppositions, and counterfactual presuppositions. Meanwhile the functions of presupposition were found five functions, twenty-one functions of presupposition, namely, conciseness functions, interestingness functions, enlargement functions, emphasis functions, and persuasion functions. In the categories of presupposition contained in the headline structures of Skin1004 selected products were dominated by the lexical presupposition with total twelve data sources found. The functions of presupposition in the headline structures of Skin1004 were dominated by the emphasis functions with total six data sources found. The accumulation of presupposition found in the headline structures of Skin1004 selected products were fifty-six presuppositions. Based on the analysis that have been conducted, the lexical presupposition and emphasis function were closely related, since it described the advantages of the products in implicit method.